KRITIK EKOLOGI DALAM “CERITA LINGKUNGAN HIDUP RAKYAT BALI” - A.A Pt Suari (Subasita: Jurnal Sastra Agama dan Pendidikan Bahasa Bali, 2023)
This study of literary ecology is one that was inspired by the current damage to the environment. The literary critique in a collection of environmental stories and how each character in those stories interacts with the environment are some of the research's limits. The literary analysis in this qualitative study employs an ecocritical approach. The data was derived from a collection of Balinese folktales called “Cerita Lingkungan Hidup Rakyat Bali” compiled by Nyoman Suarjana (1998). Following collection, the data is analysed in two stages: the first stage involves data identification, categorization, interpretation, and description; the second stage involves data verification, assessment, and conclusion. The findings of this study demonstrate that forest destruction dominates ecological harm in this short stories. As in the narrative I Lubdaka, the story characters' greedy exploits of the forest's resources are typically to blame for the destruction to the forest. Regarding I Swanangkara's attempts to conserve the forest in order to preserve its beauty and viability. Keywords: ecology, ecocriticism, Balinese short story